PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP MOTIVASI BELAJAR SISWA SD KELAS III PEMBELAJARAN BAHASA INDONESIA - Feby Kharisna; Nur Azmi Alwi; Andika Surya Perdana; Nadiah Sya’idah (Program Studi PGSD FKIP Universitas Bung Hatta, 2021)
This research aims to determine the effect of students' learning motivation through the application of the scramble learning model. This research is a research design with non-equivalent control group design, and quantitative research in the form of quasi-experimental research. This research was conducted at SDN 18 Lembah Melintang, Pasaman Barat. The population of this research is the third grade students of SDN 18 Lembah Melintang in the academic year 2021/2022. The samples of this study were 28 students in class IIIA and 26 students in class IIIB. The sampling technique used is